Increasing End-Users’ Awareness of the Environmental Impact of Software - Keller, Anne (My University, 2021)
With the growing energy demand connected to the use of data and more specifically digital services, there is action required to make the software engineering industry sustainable both now and in the future. There are different aspects to consider when talking about sustainable software. Both the aspect of developing sustainable software as well as how much you as an end-user use the software and thus how much energy you use. The goal of this thesis is to find out how it is possible, through software, to affect end-users to become more aware of the impact they have on the environment while making use of different software and at the same time make sure that future software is sustainable. The method used to reach the goal of the thesis was an exploratory case study. This consisted of a literature study to create a basis for the survey in the study. Following, based on the survey results interviews were held to deepen and broaden the knowledge gained through the survey. Finally, a checklist with suggestions on how to impact the users of software was put together based on the three previous steps. This checklist was further validated with help from a focus group. The literature review resulted in an understanding of the field and previous re search conducted. Following, the survey resulted in an understanding of the charac teristics of the end-users of digital services and software. Moving on, the interviews resulted in a deeper knowledge and understanding of what the best ways to impact the end-users to act more sustainable would be. Finally, the general outcome and contribution of the study was a checklist consisting of suggestions on how to make end-users awareness of software’s environmental impact increase as well as what to consider and what not to do in this regard. It can be concluded that there is a need to raise awareness with end-users of software for them to act more sustainable. Further, it can be concluded that there should be information provided to increase this awareness and that this, in turn, should be based on the end-user’s individual motivators. Overall, it can be concluded that the most important aspect is to through the provided checklist try and make the end-users aware that no matter what software they use, it has an impact on the environment
Keywords: Sustainability; software engineering; end-users; end-user awareness; sustainable software engineering; sustainable software; exploratory case study; environmental impact; nudging